Antiradical activities of the extract of Passiflora incarnata - Masteikova, Ruta; Bernatoniene, Jurga; Bernatoniene, Ruta; Velziene, Saule (Acta poloniae pharmaceutica, 2008)
The objective of this work was to investigate the aqueous and ethanolic extracts of passionflower and the influence of the flavonoids they contain on the antiradical activity by DPPH* and ABTS* + methods. The data show that the Passiflora extract has not only sedative but also antiradical activity. The ethanol extract catches free radicals more effectively than the water extract. The strongest antiradical effect among the investigated flavonoids (chlorogenic acid, hyperosid, isovitexin, caffeic acid, quercetin, luteolin, orentin, rutin, scutelarein, vicenin and vitexin) was predetermined by vicenin, isovitexin and orentin. The antiradical activity increases with the increase of the concentration of the mentioned materials.
Keywords: Flavonoids; Free Radical Scavengers; rostlinné extrakty; scavengery volných radikálů; flavonoidy; Plant Extracts; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; Passiflora